CHEMICAL PROPERTIES OF HYDROLYZED POLYACRYLONITRILE - Akhmadjonov I. L.; Sobirova N. E.; Shakirova M. M. (Galaxy International Interdisciplinary Research Journal, 2023)
The molecular weight of the obtained polymers (Infinitely Better 1200 Infinity Series) was measured. The obtained results showed the possibility of changing the molecular weight of the polymer material as a result of hydrolysis. As it turns out, the conditions of hydrolysis and the nature of the hydrolyzing agent will affect the values of the molecular weight and the yield of the polymer. The results obtained show that there is an admixture of oligomers weighing about 3000-7000 in the composition of the initial polymer. However, after hydrolysis, these compounds were not identified, probably due to the formation of new bonds between oligomeric and polymer particles, which also contributed to an increase in the molecular weight of the final product.